The conceptual scheme of teaching students of pedagogical universities for the implementation of cultural and educational work: the specifics of the «physical education» field - Krause A.A.; Shumenskaya S.I.; Shayakhmetova V.R. (Theory and Practice of Physical Culture, 2025)
Objective of the study is aimed at developing and theoretically substantiating a structural and functional model that ensures the readiness of future teachers specializing in the field of physical education to carry out cultural and educational work for educational purposes. Methods and structure of the study. First and second year students, including those studying in the field of Physical Education, took part in a survey organized on the basis of Perm State Humanitarian and Pedagogical University (FSBEI HE) in cooperation with the Azov State Pedagogical University (FSBEI HE). The purpose of the survey was to identify the degree of their preparedness to conduct cultural and educational work in modern educational institutions. The ability of students to choose suitable forms and methods for the implementation of this activity was also studied. The survey was aimed at assessing the potential of future teachers in the field of organizing and conducting cultural events and educational programs. Results and conclusions. In the presented work, the authors reveal the theoretical basis of the developed model, covering both elements of pedagogical professionalism and creative abilities. The structural components are analyzed in detail, in particular, the process of formation of a value system and the development of basic skills required for the effective implementation of cultural and educational activities. The functional component of the model focuses on applied methods and tools that students can use in their future work. Various approaches to the organization of educational activities aimed at creating a cultural and educational atmosphere both in the educational institution and beyond its borders, involving a variety of stakeholders, are considered. As an illustration, examples of the implementation of the model in the framework of practical training of specialists are given.